2022
DOI: 10.1371/journal.ppat.1010397
|View full text |Cite
|
Sign up to set email alerts
|

Targeting the BspC-vimentin interaction to develop anti-virulence therapies during Group B streptococcal meningitis

Abstract: Bacterial infections are a major cause of morbidity and mortality worldwide and the rise of antibiotic resistance necessitates development of alternative treatments. Pathogen adhesins that bind to host cells initiate disease pathogenesis and represent potential therapeutic targets. We have shown previously that the BspC adhesin in Group B Streptococcus (GBS), the leading cause of bacterial neonatal meningitis, interacts with host vimentin to promote attachment to brain endothelium and disease development. Here… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 72 publications
(96 reference statements)
0
12
0
Order By: Relevance
“…We have previously shown that BspC is necessary and sufficient to induce neutrophil chemokine signaling in brain endothelial cells and during the progression of meningitis in vivo ( 15 , 16 ). As neutrophil influx is associated with chorioamnionitis and preterm labor after bacterial ascending infection ( 8 , 26 to 28 ), we sought to investigate the proinflammatory potential of BspC within this niche.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…We have previously shown that BspC is necessary and sufficient to induce neutrophil chemokine signaling in brain endothelial cells and during the progression of meningitis in vivo ( 15 , 16 ). As neutrophil influx is associated with chorioamnionitis and preterm labor after bacterial ascending infection ( 8 , 26 to 28 ), we sought to investigate the proinflammatory potential of BspC within this niche.…”
Section: Resultsmentioning
confidence: 99%
“…We recently determined that the BspC V-domain binding pocket was critical for BspC-dependent interaction with brain endothelial cells and vimentin ( 15 ). We hypothesized that the V-domain may similarly contribute to BspC-mediated adherence to FRT cells, auto-aggregation, and K19 interaction.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations